Synthesis, Characterization and Thermal Analysis of Lanthanide(III) Nitrates Complexes of Schiff Base Derived From o-Vanillin and p-Toluidine - Hangming, Guo (Asian Journal of Chemistry, 2010)
A series of 6 complexes were synthesized using lanthanide(III) nitrates with Schiff base (L) 2-[(4-methylphenylimino)methyl]-6-methoxyphenol from o-vanillin and p-toluidine and characterized by elemental analysis, molar conductance, infrared spectra, thermal analysis. Their chemical formula are [LnL2(NO3)3] (Ln = Dy, Ho, Er, Tm, Yb, Y). The central Ln(III) ion in the complexes coordinates with both two L via 4 oxygen atoms of the phenol hydroxy groups and methoxy groups and 3 bidentate nitrates via their 6 oxygen atoms. Their coordination numbers are 10. The thermal behaviour of these complexes has been studied by TG and DTG. These complexes show 4 steps weight loss and show almost similar mode of decomposition. The residues after heating correspond to metal oxide Ln2O3.